Diet of solitary males Boreal Owls Aegolius funereus in the lowlands of the Bydgoszcz Forest (northern Poland) - Kasprzyk, Krzysztof Andrzej; Frątczak , Waldemar (Ecological Questions, 2025)
The Boreal Owl is one of the owl species that has been observed to increase its range, mainly in Central Europe. This paper presents information on the diet diversity of solitary males in newly colonised areas in northern Poland. The authors believe that colonised commercial forests represent suboptimal habitats in terms of nutritional conditions. The research was carried out in a commercial forest with old-growth pine stands being left intact for Black Woodpecker tree holes. Pellets were collected under a Norway spruce tree near a tree hole occupied by a solitary male; no females or young were observed during this period. The analysis of pellets revealed that the diet of owls consists mainly of small mammals. However, they consume significantly fewer voles (Microtus and Myodes) compared to Boreal Owls from the north of the species’ range, and representatives of insectivores (Sorex araneus and S. minutus) predominate in their diet in terms of relative abundance. Among rodents, Apodemus sylvaticus is the most abundant in the owls’ diet and, together with other murids, dominates in terms of biomass consumed. Boreal Owls also supplement their diet with birds and small bats, which indicates food plasticity. This also suggests a possible strategy of males inhabiting the few tree hollows in this area and successful breeding in years with more abundant rodent populations, which has been confirmed by other studies carried out in this area.